2017
DOI: 10.2298/abs170210014v
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of copper tolerance and accumulation in Populus nigra

Abstract: Phytoextraction is an efficient and cheap way to extract copper from soils in riparian zones. In this work five genotypes of the endangered tree species Populus nigra L. were tested for their copper tolerance and accumulation in vitro when cultivated on media with three Cu concentrations: 10-3 , 10-4 and 10-7 M (buffered with citric acid/Na-citrate buffer, pH 3 before sterilization). After five-weeks cultivation of rooted shoots, the highest increases in morphological and biomass parameters were observed at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…High concentrations of HM such as cadmium (Cd), lead (Pb), chromium (Cr), copper (Cu), and mercury (Hg) produce toxic effects on soil processes [3]. To eliminate HM from contaminated soils, metal-accumulator plants have been used as a novel eco-friendly and cost-effective approach, referred to as phytoremediation [4].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of HM such as cadmium (Cd), lead (Pb), chromium (Cr), copper (Cu), and mercury (Hg) produce toxic effects on soil processes [3]. To eliminate HM from contaminated soils, metal-accumulator plants have been used as a novel eco-friendly and cost-effective approach, referred to as phytoremediation [4].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the results gained by Kovačević et al (2013a) on media with pH 5.5, it can be assumed that a stronger effect of lead in our work was achieved by lowering pH and using citric acid. Likewise, Vuksanović et al (2017b) gained toxic effect and total absence of rooting of Populus nigra in medium with pH 3 and 10 -3 M Cu 2+ , while di Lonardo et al (2011) reported absence of toxic effect on Populus alba for the same concentration of copper in medium with pH 5.2.…”
Section: Discussionmentioning
confidence: 93%
“…This is the first study to demonstrate evidence of Cu 2+ effects on morphological, physiological and biochemical variables in C. quitensis. Vuksanović et al (2017) [39] study five different European black poplar (Populusnigra L.) genotypes were studied in vitro for their tolerance to Cu 2+ based on morphological parameters, biomass accumulation and pigment content, as well as Cu 2+ accumulation in aboveground plant parts. Also, the effect of the pH of the medium and Cu 2+ concentration was examined in order to optimize the evaluation of Cu 2+ tolerance in vitro.…”
Section: Discussionmentioning
confidence: 99%